Two-dimensional (2D) materials for biomedical applications - Gengxin Wu; Brea B. Yang; Ying-Wei Yang (APL Materials)
Two-dimensional (2D) materials with unique structural and physicochemical properties have emerged as a powerful toolbox in biomedical applications. Nanoscale inorganic, organic, and hybrid 2D materials have shown exceptional potential in biosensing, drug delivery, tissue engineering, and cancer therapeutics. Their ultrahigh specific surface area, remarkable functionalization capabilities, and distinctive optoelectronic characteristics enable sophisticated interactions with biological systems. This Editorial covers the synthesis methods, characteristic properties, and emerging biomedical applications of 2D materials, with a particular focus on their potential in cancer theranostics and biosensing. It also highlights the critical challenges in clinical translation.